A monista felfogás érvényesülése a szerzői jogi törvényben - Petkó, Mihály (Debreceni Jogi Műhely, 2005)
Examining the history of copyright law, we can distinct two significant theories. The distinction is based upon the position of entitled parties. Two separated fields can be found among the rights of the author: personal and financial rights. It is no doubt that personal rights are inseparable from the author itself, these rights cannot become objects of commercial businesses. If we look at these rights a little bit closer, we can realize that personal rights of the author do not play significant role in earning money from an intellectual product. These rights ensure the integrity and originality of works. Separating the two theories we have to focus on financial rights. Trying to describe these rights we can see that no exact definition can be given to them because of the permanent development of printing and publishing technology. Due to the monist theory it can be said that financial rights are close to personal ones, they are inseparable from personality of the author. Transcribing this opinion to the language of law it means that the decent regulation should prohibit the transfer of these rights among living persons. In the Anglo-Saxon legal system experts think that financial rights have to take part in commercial trade if we want to acknowledge the achievement of authors. In Hungary copyright law is on the point of the monist theory. The Act refers that financial rights of the author cannot be transferred and the author has no right to abandon them. If we get a closer look at the structure of the valid Act, we can say that monist theory is not consistent. It is possible to inherit financial rights. We need this rule if we would like to harmonize the system to the time of protection. The other relevant fact of crossing the prohibition is in connection with works created under labour frames. In this case the employer gets financial rights ex lege. To find the reason of this regulation we have to examine the nature and aim of labour relations. The employer gives payment to his employee, the author to establish and create works. In this situation it is natural that the author looses his financial rights. The problem is that in Hungary differences can be found between civil and labour law. If we try to give meaning to labour relations, misunderstandings and different point of views can reveal. The other problematic factor is that the Act does not bother with the question of succession. In my study I present the pros and cons of both theories and gather those significant practical and theoretical fields of copyright law that can be limits of monist theory. I examine special rules for special works, rules of civil and labour law in connection with authors and give a short historical overview to see what can be the main directions of future developments.